From the American Civil War to the War on Terror - Hartz, Emily. author. aut Link
X, 114 p.
Keywords: This book offers a systematic and comprehensive account of the key cases that have come to shape the jurisprudence on emergency law in the United States from the Civil War to the War on Terror. The legal questions raised in these cases concern fundamental constitutional issues such as the status of fundamental rights, the role of the court in times of war, and the question of how to interpret constitutional limitations to executive power. At stake in these difficult legal questions is the issue of how to conceive of the very status of law in liberal democratic states. The questions with which the Supreme Court justices have to grapple in these cases are therefore as philosophical as they are legal. In this book the Court's arguments are systematized according to categories informed by constitutional law as well as classic philosophical discussions of the problem of emergency. On this basis, the book singles out three legal paradigms for interpreting the problem of emergency: the rights model, the extra-legal model and the procedural model. This systematic approach helps the reader develop a philosophical and legal overview of central issues in the jurisprudence on emergency.